Plasma exosomal miR-199a-3p downregulates cell proliferation and migration in Hirschsprung’s disease by targeting mTOR - Daiyue, Yu; Yang, Yang; Zhaorong, Huang; Yi, Lu; Chen, Wang; Caiyun, Luo; Yuqian, Su; Liucheng, Yang; Kai, Wu (Pediatric surgery international, 2022)
Background Plasma exosomal microRNAs have been suggested to be potential biomarkers of disease. However, the exosomal microRNAs in Hirschsprung’s disease (HSCR) are still unclear. In this study, we analyzed the miRNA profiles of HSCR and elucidated the mechanism of the selected miR-199a-3p in the development of HSCR. Methods Plasma exosomes were isolated, and exosomal miRNA high-throughput sequencing was performed to obtain differentially expressed miRNAs. CCK-8 and Transwell assay were used to determine the function of the most differentially expressed miRNA, which was confirmed in tissue specimen. Thereafter, target genes of the selected miRNAs were predicted by the databases. Gene Ontology (GO) analysis, Kyoto Encyclopedia of Genes Genomes (KEGG) analysis, and protein–protein interaction network (PPI) construction of possible target genes were used to perform enrichment analysis and interaction. Finally, the PCR, Western blot and recovery experiment were used to confirm the function of target gene, mammalian target of rapamycin (mTOR), in vitro. Results The expression of miR-199a-3p was upregulated in plasma exosomes and diseased colonic tissues of patients with HSCR. In vitro, miR-199a-3p can inhibit cell proliferation and migration . Bioinformatic analysis suggested that mTOR might be a potential target of miR-199a-3p in HSCR. mTOR was discovered to be downregulated by miR-199a-3p in vitro. The negative connection between mTOR and miR-199a-3p was confirmed in tissue samples. mTOR can partially reverse the effect of miR-199a-3p on cell proliferation and migration function in vitro. Conclusions miR-199a-3p suppresses cell growth and motility, partially by targeting mTOR. Plasma exosomal miR-199a-3p, a diagnostic marker, is crucial for the development of HSCR.